Affective coding: the emotional dimension of agency - Gentsch, Antje; Synofzik, Matthis (Frontiers in Human Neuroscience, 2014)
The sense of agency (the registration that I am the initiator and controller of my actions and relevant events) is associated with several affective dimensions. This makes it surprising that the emotion factor has been largely neglected in the field of agency research. Current empirical investigations of the sense of agency mainly focus on sensorimotor signals (efference copy) and cognitive cues (intentions, beliefs) and on how they are integrated. Here we argue that this picture is not sufficient to explain agency experience, since agency and emotions constantly interact in our daily life by several ways. Reviewing first recent empirical evidence, we show that self-action perception is in fact modulated by the affective valence of outcomes already at the sensorimotor level. We hypothesize that the “affective coding” between agency and action outcomes plays an essential role in agency processing, i.e. the prospective, immediate or retrospective shaping of agency representations by affective components. This affective coding of agency be differentially altered in various neuropsychiatric diseases (e.g. schizophrenia vs. depression), thus helping to explain the dysfunctions and content of agency experiences in these diseases.